KEMAMPUAN SISWA DALAM MENULIS TEKS DEBAT DENGAN PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK PENINGKATAN BERPIKIR KRITIS PADA SISWA KELAS X SMAN 9 BANDUNG - Adisti Ayuningtias; Panca Pertiwi Hidayati; Setiawan (STKIP Subang, 2023)
This research is motivated by the low ability of students in writing and the difficulty of students in writing, especially in writing debate text. One of the factors that cause this is that students find it difficult to determine the first word, besides that students are also unable to express their ideas. As well as the lack of use of innovative and creative learning models by educators. One of the learning models that can be used is, problem-based learning model can be used as an alternative to be used in learning to write debate text. The purpose of this study was to determine the ability of students in writing debate text with the application of the Problem Based Learning model. The approach used in this research is a quantitative approach. The results of this study will discuss the data that the authors have collected from the subjects and objects of research, the results of data processing, and data processing analysis. The author has compiled the results of this study after conducting research on class X students. there are X-4 classes as experimental classes and X-5 classes as control classes. The average results of the experimental class prates were 55.96 which then increased in the post-test average results to 76.92 with a percentage increase of 37.4%. While the average result of the control class prates was 53.27 which increased in the post-test average of 69.61 with a percentage increase of only 29%. Judging from the average value data that the author has found, it can be concluded that experimental class students are better able to write debate texts with the application of problem-based learning models. In addition, through the use of problem-based learning models can also improve students' critical thinking skills with a percentage difference of 10.5%.